1912
DOI: 10.1039/ct9120101459
|View full text |Cite
|
Sign up to set email alerts
|

CLVI.—The influence of colloids and fine suspensions on the solubility of gases in water. Part II. Solubility of carbon dioxide and of hydrogen

Abstract: IN a paper by Findlay and Creighton (Trans., 1910, 97, 536) the results of an investigation of the solubility of carbon dioxide and nitrous oxide in water in presence of colloids and fine suspensions were communicated. I n view of the results then obtained it was decided to continue the investigation; and for the purpose of ascertaining in how far the behaviour of colloids is a peculiar one, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1931
1931
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“… (a,b). Comparison of the experimental CO 2 solubility in various aqueous salt solutions at 298.15 K and 0.1 MPa based on different concentration scales: (a) percent of salt by weight; (b) ionic strength. Solid lines represent the calculated values from the PSUCO2 model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… (a,b). Comparison of the experimental CO 2 solubility in various aqueous salt solutions at 298.15 K and 0.1 MPa based on different concentration scales: (a) percent of salt by weight; (b) ionic strength. Solid lines represent the calculated values from the PSUCO2 model.…”
Section: Discussionmentioning
confidence: 99%
“… (a–d). Comparison of the model calculations against the experimental CO 2 solubility , , in aqueous KCl solutions. (a) 0.1 MPa, 288–313 K, 0–4.75 mol kg −1 KCl; (b) 0.4–9.1 MPa, 314–433 K, and 2 mol kg −1 KCl; (c) 0.6–9.4 MPa, 313–433 K, and 4 mol kg −1 KCl; (d) Comparison of the experimental CO 2 solubility between Pérez‐Salado Kamps and Kiepe et al at the same P‐T‐x conditions, the modeling results are in excellent agreement with the experimental results reported by Pérez‐Salado Kamps …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findlay and Shan (29) investigated the effect of colloids and fine suspensions on the solubility of CO 2 in water. The results were in harmony with…”
Section: ~-mentioning
confidence: 99%
“…It is reported that pure CO 2 clathrate hydrate decomposed to metastable super-cooled water below the water freezing temperature 17 . Although CO 2 solubility in trehalose aqueous solution was not found in the literature, it is reported that CO 2 solubility both in sucrose aqueous solution 18 and in glucose aqueous solution 19 were lower than that in pure water and decreased with an increase in concentration of sucrose and glucose in solution. CO 2 solubility in the sucrose solution with sucrose mass fraction of 0.12 18 and in the glucose solution with glucose mass fraction of 0.12 19 are approximate 10% and 20% lower than that in pure water, respectively.…”
Section: Resultsmentioning
confidence: 86%